Algorithm of active TB case finding in intervention group. - Xiaolin Wei (287892) (2025)
a. TB Symptoms include chronic cough over 2 weeks, hemoptysis, fever, night sweats, chest pain or unexplained weight loss. TB = tuberculosis, DR = digital radiography.